Recycling potential of waste materials as fire resistance material - Ayu Wazira, Azhari; Abdul Haqi, Ibrahim; Mahyun, Ab Wahab; Salwa, Mohd Zaini Makhtar; Azmil, Mohd Aris (Universiti Teknologi Malaysia (UTM), 2011)
The 2nd International Conference and Workshops on Basic and Applied Science (2nd ICOWOBAS) Regional Annual Fundamental Science Seminar (RAFSS 2009) organized by Universiti Teknologi Malaysia, from 2nd - 4th June 2009 at The Zone Regency Hotel, Johor Bahru, Johor, Malaysia.